2014
DOI: 10.1016/j.contraception.2014.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of self versus clinical administration of subcutaneous depot medroxyprogesterone acetate

Abstract: Objectives To evaluate feasibility, acceptability, continuation, and trough serum levels following self-administration of subcutaneous (SC) depot medroxyprogesterone acetate (DMPA). Study Design Women presenting to a family planning clinic to initiate, restart, or continue DMPA were offered study entry. Participants were randomized in a 2:1 ratio to self or clinician administered SC DMPA 104mg. Those randomized to self-administration were taught to self-inject and were supervised in performing the initial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 15 publications
(20 reference statements)
1
38
0
1
Order By: Relevance
“…However, the scarcity of pregnancies at intervention discontinuation visits is consistent with continued use of DMPA-SC in the periods that women reported adhering to DMPA-SC. In a randomised study of Depo-subQ Provera 104 in New York, 17 all women who reported continuation had MPA concentrations in the contraceptive range, although the investigators did not find a difference in continuation rates between self-administration and clinicadministration groups. This absence of a difference was possibly because women had to return to the clinic to provide blood specimens, thus hindering one of the anticipated benefits of self-administration.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the scarcity of pregnancies at intervention discontinuation visits is consistent with continued use of DMPA-SC in the periods that women reported adhering to DMPA-SC. In a randomised study of Depo-subQ Provera 104 in New York, 17 all women who reported continuation had MPA concentrations in the contraceptive range, although the investigators did not find a difference in continuation rates between self-administration and clinicadministration groups. This absence of a difference was possibly because women had to return to the clinic to provide blood specimens, thus hindering one of the anticipated benefits of self-administration.…”
Section: Discussionmentioning
confidence: 95%
“…This absence of a difference was possibly because women had to return to the clinic to provide blood specimens, thus hindering one of the anticipated benefits of self-administration. 17 The requirement for pregnancy tests might have encouraged women to report their continuation status more accurately during our trial. Another possibility is that women in the provider-administered group might be less likely to overreport continuation than those in the self-injection group if they thought that we could follow up with the providers to confirm re-injection-something that we could not do for women in the self-injection group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified a total of 8926 unique citations, and of those citations, 44 underwent full‐text review. Three studies, one randomised controlled trial (RCT) and two prospective cohort studies, met the inclusion criteria for this review (Figure ) . Two studies evaluated the self‐administration of DMPA SC, compared with DMPA SC or DMPA IM administered by a healthcare provider; the third study included women self‐administering versus nurse administration of a combined hormonal contraceptive IM injectable .…”
Section: Resultsmentioning
confidence: 99%
“…The study design contributed to the serious risk of bias for two studies (Table ). Low‐certainty evidence shows that there was little or no difference in continuation rates when women self‐administered contraceptive injections in the RCT . For the two non‐RCT trials, the effect of the intervention on the continuation rate was uncertain because the certainty of the evidence was assessed as very low .…”
Section: Resultsmentioning
confidence: 99%